The predictive value of diaphragm ultrasound for weaning outcomes in critically ill children - Yang Xue; Zhen Zhang; Chu-Qiao Sheng; Yu-Mei Li; Fei-Yong Jia (BMC Pulmonary Medicine, 2019)
Abstract Introduction Multiple studies have shown that diaphragmatic ultrasound can better predict the outcome of weaning in adults. However, there are few studies focusing on children, leading to a lack of sufficient clinical evidence for the application of diaphragmatic ultrasound in children. The purpose of this study was to investigate the predictive value of diaphragm ultrasound for weaning outcomes in critically ill children. Methods The study included 50 cases whose mechanical ventilation (MV) time was > 48 h, and all eligibles were divided into either the weaning success group (n = 39) or the weaning failure group (n = 11). Diaphragm thickness, diaphragmatic excursion (DE), and diaphragmatic thickening fraction (DTF) were measured in the zone of apposition. The maximum inspiratory pressure (PImax) was also recorded. Results The ventilatory treatment time (P = 0.002) and length of PICU stay (P = 0.013) in the weaning failure group was longer than the success group. Cut-off values of diaphragmatic measures associated with successful weaning were ≥ 21% for DTF with a sensitivity of 0.82 and a specificity of 0.81, whereas it was ≥0.86 cm H2O/kg for PImax with a sensitivity of 0.51 and a specificity of 0.82. The linear correlation analysis showed that DTF had a significant positive correlation with PImax in children (P = 0.003). Conclusions Diaphragm ultrasound has potential value in predicting the weaning outcome of critically ill children. DTF and PImax presented better performance than other diaphragmatic parameters. However, DE has limited value in predicting weaning outcomes of children with MV. Trial registration Current Controlled Trials ChiCTR1800020196, (Dec 2018).